The Relationship Between Emotion Regulation and Academic Procrastination Among Students at SMPN X Bekasi City - Tri Mutia Chusnul Khotimah; Nurwahyuni Nasir; Hema Dayita (Inovan Publisher, 2026)
Academic procrastination is a tendency to delay completing academic tasks that is commonly found among junior high school students and may negatively affect academic performance. One psychological factor that is associated with academic procrastination is emotion regulation. This study aimed to examine the relationship between emotion regulation and academic procrastination among students at SMPN 40 Kota Bekasi. This study employed a quantitative approach with a correlational design. The participants consisted of 301 seventh- and eighth-grade students selected using convenience sampling. Data were collected using an emotion regulation scale and an academic procrastination scale. Data were analyzed using the Spearman Rank correlation test. The results revealed a significant negative relationship between emotion regulation and academic procrastination (r = -0.135; p = 0.019). These findings indicate that students with better emotion regulation tend to exhibit lower levels of academic procrastination. However, the correlation was relatively weak, suggesting that academic procrastination is also influenced by other psychological and environmental factors beyond emotion regulation. This study concludes that emotion regulation is significantly associated with academic procrastination among junior high school students at SMPN 40 Kota Bekasi.